2018
DOI: 10.1186/s40164-018-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

PAN3–PSMA2 fusion resulting from a novel t(7;13)(p14;q12) chromosome translocation in a myelodysplastic syndrome that evolved into acute myeloid leukemia

Abstract: BackgroundAcquired primary chromosomal changes in cancer are sometimes found as sole karyotypic abnormalities. They are specifically associated with particular types of neoplasia, essential in establishing the neoplasm, and they often lead to the generation of chimeric genes of pathogenetic, diagnostic, and prognostic importance. Thus, the report of new primary cancer-specific chromosomal aberrations is not only of scientific but also potentially of clinical interest, as is the detection of their gene-level co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Three recurrent gene mutations (RUNX1, ASXL1, and TP53) have been added in the risk stratification of the ELN-2017 recommendations for AML [2]. Recently, more novel fusion genes, such as GTF2I-PDGFRB and IKZF1-TYW1 fusion genes, and PAN2/PAN3 complex, have reported and may be clinically important [120,121]. As the new technology advances, more recurrent gene mutations will be explored and used for AML risk stratification and treatment guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Three recurrent gene mutations (RUNX1, ASXL1, and TP53) have been added in the risk stratification of the ELN-2017 recommendations for AML [2]. Recently, more novel fusion genes, such as GTF2I-PDGFRB and IKZF1-TYW1 fusion genes, and PAN2/PAN3 complex, have reported and may be clinically important [120,121]. As the new technology advances, more recurrent gene mutations will be explored and used for AML risk stratification and treatment guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has reported that the gene PAN3 is considered a candidate gene located in amplified chromosome regions in AML patients with a complex karyotype [21]. In a myelodysplastic syndrome patient that evolved into AML, a fusion of PAN3 with the gene PSMA2 was formed from a chromosome translocation [29], suggesting a potential association between the PAN3 gene and AML development. As further evidence addressing the role of PAN3 in AML, our in vitro experiments found that downregulation of circ-PAN3 by siRNA considerably increased the sensitivity of drug-resistant THP-1/ADM cells to ADM; however, after histopathological examination, a significantly higher expression level of circPAN3 was observed in the BM samples from refractory/recurrent AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many chromosome translocations resulting in truncated or fused genes leading to out-of-frame transcripts have been reported only once. These events might turn out to be recurrent if and when the second case, and then the third et cetera, is reported, as for the leukemias with t(8;19)/KAT6A::LEUTX described between 1988 and 1995 and t(11;20)/ZMYND8::RELA between 2013 and 2018 (33,37,38,40,53,67,(89)(90)(91)(92)(93)(94)(118)(119)(120)(121). In 1985, De Braekeleer and coworkers reported an acute lymphoblastic leukemia carrying a t(10;19)(q26;q13) as the sole cytogenetic change (122).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 99%
“…The reality of these gene fusions is then confirmed (or ruled out) using yet other methods such as FISH, PCR, and Sanger sequencing analyses (33,45,77,(84)(85)(86)(87)(88). This approach also has the advantage of not overlooking "non-canonical" fusion genes or rearranged genes that lead to truncated proteins (42,51,58,(89)(90)(91)(92)(93)(94).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 99%